Integer Relaxation on Binary Quadratic Programming for Batching and Sequencing in Single Formulation to Minimize Total Actual Flow Times Criteria - Zahedi, Zahedi (Bina Nusantara University, 2011)
This paper examines batch scheduling problem that has batching and sequencing in single formulation for multiple-item case. The first step is to develop a model for single item single resource discussed in Zahedi (2008). The model determined batch sizes and their schedule simultaneously in single item case. This paper develops the model and algorithm for multiple-item case. The model functions to minimize total actual flow times. An algorithm for the model is developed using a relaxation of the binary constraints. The binary values for the decision variables are obtained from steps provided in algorithm. A numerical experience showing characteristics of this problem is presented.